Lanark. A Life in 4 Books - Gray A. Alasdair (London, Picador, 1985)
From the moment it first appeed, Lanark was hailed as the most remarkable novel of the second half of the 20th century. A work of extraordinary imagination and wide range, its playful narrative techniques convey a profound message, both personal and political, about humankinds inability to love, and yet our compulsion to go on trying. With its echoes of Dante, Blake, Joyce, Kafka and Lewis Carroll, Lanark has been translated into over a dozen languages to world-wide success. This paperback edition marks the novels return to its original publisher as the 100th title to appear in the influential Canongate Classics series.